Bioenergy biomass to biofuels - Dahiya, Anju; Dahiya, Anju. (amsterdam : academic press, 2015)
"Bioenergy: Biomass to Biofuels examines all current and emerging feedstocks and the advanced processes and technologies enabling the development of their end products, ranging from solid (wood energy, grass energy, and other biomass) to liquid (biodiesel from oil seed crops, algae biofuel, waste-oil, ethanol etc.) and gaseous/electric (biogas, syngas, bioelectricity). Life cycle analysis, Energy Return on Energy Invested (EROI), integrated sustainability assessments, environmental, economic, and social issues are all given thorough consideration. Guest authors from industry and academia contribute their expertise to ensure you obtain the most nuanced, comprehensive information. Quizzes, case studies and project ideas will help you to master the technological details included, and connect theory to real-world implementation. Whether you are a professional entering the field, a student exploring the pathways from biomass to biofuels, or an instructor developing a course on biofuels, this book will educate you about the trade-offs between various feedstocks, provide helpful evaluation criteria for biofuel project proposals, and provide a one-stop information resource on the hottest new advances in the field, all presented in clear language, and within a practical context that will give you a bird's eye view, from the field to the refinery and beyond"--
Includes bibliographical references and index.
Keywords: Biomass energy